Lyme Disease: In the “Lime Light” for Over 25 Years - J Evans, Kenisha; Ayers, Eric; E. Stinson, Cassandra; E Simpson, Arren; Quayson, Delisa (Journal of Family Medicine, 2019)
Lyme disease has been a topic of debate practically since its discovery in the 1970’s. The hot topic is whether or not long-term antibiotics should be used for Lyme disease patients with persistent symptoms. The source of such a long-running debate stems from the difference in opinions over the cause of long-term, persistent symptoms after treatment in some patients. Toward its end, Medicine has finally begun to embrace the existence of Chronic Lyme Disease, but changes still need to be made in the future.
Keywords: Lyme disease; Ixodes ricinus complex; juvenile rheumatoid arthritis